Variability of the Chemical Composition of Cork - Pereira, Helena (BioResources, 2013)
The chemical composition of cork was determined, following a sampling that covered the whole production area in Portugal (29 provenances from six regions) with samples taken at cork stripping. To analyse between population variations, a more intensive sampling was made in two locations. The overall mean chemical composition of cork was: extractives 16.2% (dichloromethane 5.8%, ethanol 5.9%, water 4.5%), suberin 42.8% (long-chain lipids 41.0%, glycerol 3.8%), and lignin 22.0% (Klason 21.1%, acid soluble 0.9%). The suberin compositional ratio of long chain lipids to glycerol, LCLip:Gly, was 11.3. The proportion of neutral sugars in the polysaccharides was: glucose 46.1%, xylose 25.1%, arabinose 18.0%, mannose 3.0%, galactose 7.3%, and rhamnose 0.5%. The range of values was large and the variation between individual trees seemed to be the major factor of the differences. Geographical location of cork production was statistically significant only in a few cases when considering site and not when considering regions. The population variation in two sites was important and the absolute difference between the site mean values was small. This research covers the natural variability of cork’s chemical composition and discusses the contribution of the structural compounds to the variation of cork properties.
Keywords: chemical composition; Cork; Extractives; Lignin; Quercus suber; suberin

INFLUENCIA DE LA "MANCHA AMARILLA" SOBRE LA COMPOSICIÓN QUÍMICA DEL CORCHO Y LA PRESENCIA DE TCA - García Vallejo, M. C.; Varea, S.; Cadahia, E.; Fernández de Simón, B. (III Congreso Forestal Español, 2001)
The anomaly of cork known as "yellow stain" has been considered as the main responsible for the presence, in some cork stoppers, of 2,4,6-trichloroanisole (TCA), compound that confers the "cork taint" to wine. In this Communication, a comparative study on the chemical composition of cork (suberin, waxes, polyphenols, holocellulose and lignin) and on the presence of chloroanisoles and chlorophenols is carried out with samples of healthy cork and cork affected with that anomaly. The cork with "yellow stain" differed from the healthy cork because of the presence of TCA and the low content of tannins.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español issue: 1995 pub-location: Granada
Keywords: chemical composition; Cork; yellow stain

INFLUENCIA DE LA "MANCHA AMARILLA" SOBRE LA COMPOSICIÓN QUÍMICA DEL CORCHO Y LA PRESENCIA DE TCA - García Vallejo, M C; Varea, S; Cadahía, E; Fernández de Simón, B (III Congreso Forestal Español, 2001)
The anomaly of cork known as "yellow stain" has been considered as the main responsible for the presence, in some cork stoppers, of 2,4,6-trichloroanisole (TCA), compound that confers the "cork taint" to wine. In this Communication, a comparative study on the chemical composition of cork (suberin, waxes, polyphenols, holocellulose and lignin) and on the presence of chloroanisoles and chlorophenols is carried out with samples of healthy cork and cork affected with that anomaly. The cork with "yellow stain" differed from the healthy cork because of the presence of TCA and the low content of tannins.
Keywords: chemical composition; Cork; yellow stain

Cuticular waxes of the holm (Quercus ilex l. subsp. ballota (desf.) samp.) and cork (Q. suber l.) oaks - Martins, C M C; Mesquita, S M M; Vaz, W L C (Phytochemical Analysis, 1999)
The epicuticular leaf waxes of young leaves of the Holm oak (Quercus ilex L. ssp. ballota (Desf.) Samp.) and the cork oak (Q suber L.) were extracted in chloroform and separated into their constituent wax classes by preparative thin layer and high pressure liquid chromatography. The wax coverage was about 125 μg/cm2 in Q. suber and about 71 μg/cm2 in Q. ilex. The main classes encountered (by weight) were odd chain n-alkanes (9% in Q. ilex, and 4–27% in Q. suber) and even chain amphiphilic compounds. The major classes of amphiphilic compounds were n-alkan-1-ols (20–27% in Q. ilex, and 18–50% in Q. suber), n-alkanals (<3% in Q. ilex, and up to 25% in Q. suber), n-alkanoic acids (11–12% in Q. ilex, and <5% in Q. suber) and n-alkyl esters (50–56% in Q. ilex, and 25–45% in Q. suber). The major components of each class, identified by gas chromatography coupled to mass spectrometry were C29 for the n-alkanes (54–58% in Q. ilex, and 47–57% in Q. suber), C24 for the n-alkan-1-ols (78–87% in Q. ilex, and 77–93% in Q. suber), C30 for the n-alkanals (up to 57% in Q. ilex, and up to 77% in Q. suber), C22 and C24 for the n-alkanoic acids in Q. ilex (39–62%) and C30 in Q. suber (49%). The n-alkyl esters were composed mainly from C22 and C24n-alkanoic acids (∼38%) and n-alkan-1-ols (43–54%) in Q. ilex, whereas in Q. suber these esters were composed mainly from C22 and C24n-alkanoic acids (44–52%) and C20 and C22n-alkan-1-ols (32–66%). In addition to the above compounds, trace amounts (<5%) of C28 and C30n-alkenes and the triterpenone, friedelin, were encountered in Q. suber and both plant waxes contained small amounts of the triterpenols α- and β-amyrin (5–9% of the total alkanol content). The variability observed in the chemical composition of the leaf waxes were attributable to seasonal causes and/or leaf age. Copyright © 1999 John Wiley & Sons, Ltd.
Keywords: chemical composition; cuticle; cuticular waxes; Quercus ilex; Quercus suber

Cuticular waxes of the holm (Quercus ilex l. subsp. ballota (desf.) samp.) and cork (Q. suber l.) oaks - Martins, C. M. C.; Mesquita, S. M. M.; Vaz, W. L. C. (Phytochemical Analysis, 1999)
The epicuticular leaf waxes of young leaves of the Holm oak (Quercus ilex L. ssp. ballota (Desf.) Samp.) and the cork oak (Q suber L.) were extracted in chloroform and separated into their constituent wax classes by preparative thin layer and high pressure liquid chromatography. The wax coverage was about 125 μg/cm2 in Q. suber and about 71 μg/cm2 in Q. ilex. The main classes encountered (by weight) were odd chain n-alkanes (9% in Q. ilex, and 4–27% in Q. suber) and even chain amphiphilic compounds. The major classes of amphiphilic compounds were n-alkan-1-ols (20–27% in Q. ilex, and 18–50% in Q. suber), n-alkanals (<3% in Q. ilex, and up to 25% in Q. suber), n-alkanoic acids (11–12% in Q. ilex, and <5% in Q. suber) and n-alkyl esters (50–56% in Q. ilex, and 25–45% in Q. suber). The major components of each class, identified by gas chromatography coupled to mass spectrometry were C29 for the n-alkanes (54–58% in Q. ilex, and 47–57% in Q. suber), C24 for the n-alkan-1-ols (78–87% in Q. ilex, and 77–93% in Q. suber), C30 for the n-alkanals (up to 57% in Q. ilex, and up to 77% in Q. suber), C22 and C24 for the n-alkanoic acids in Q. ilex (39–62%) and C30 in Q. suber (49%). The n-alkyl esters were composed mainly from C22 and C24n-alkanoic acids (∼38%) and n-alkan-1-ols (43–54%) in Q. ilex, whereas in Q. suber these esters were composed mainly from C22 and C24n-alkanoic acids (44–52%) and C20 and C22n-alkan-1-ols (32–66%). In addition to the above compounds, trace amounts (<5%) of C28 and C30n-alkenes and the triterpenone, friedelin, were encountered in Q. suber and both plant waxes contained small amounts of the triterpenols α- and β-amyrin (5–9% of the total alkanol content). The variability observed in the chemical composition of the leaf waxes were attributable to seasonal causes and/or leaf age. Copyright © 1999 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd.
Keywords: chemical composition; cuticle; cuticular waxes; Quercus ilex; Quercus suber

Post forest-fire hydrochemical behaviour of the Rimbaud catchment (Massif des Maures, France) - Martin, C; Chevalier, Y (ZEITSCHRIFT FUR GEOMORPHOLOGIE, 1999)
In August 1990, a forest fire devastated 84 % of the Rimbaud catchment area (1.46 km(2)). This catchment presents a substratum composed of gneiss. Its relief is sharp. Soils are skeletal. The forest fire destroyed a maquis (with treelike heather and arbustus) interspersed with cork oaks and maritime pines. The fire's effects on the chemical composition of the runoff have remained light in terms of low flows. On the other hand, mineralization has greatly increased during flood, especially at the beginning of the 1990-91 water year. The paper reports on the observations conducted during four years after the fire. Dissolved outputs and hydrochemical balances are compared with results obtained on the same catchment before the forest fire, and on the Boussicaut catchment (0.74 km(2)), which is very close by, but which was not burnt.
APS
Keywords: chemical composition; Cork oak; forest fire; Maquis; maritime pine; runoff

Chemical Characterization of Reproduction Cork from Spanish Quercus Suber - Conde, Elvira; Cadahía, Estrella; Garcia-Vallejo, Maria Conceptión; Gonźalez-Adrados, José Ramón (Journal of Wood Chemistry and Technology, 1998)
Abstract The chemical composition of Quercus suber reproduction cork was studied in planks from three different trees at different stages of their industrial processing and in samples collected in seven locations in the three main Spanish production areas. Extracts in chloroform, methanol and water, ne[ugrave]tral and acid fractions of waxes, suberin, lignin, holocellulose and pentosans, and polyphenols (low molecular weight polyphenols and tannins), were quantified. Suberin was the main component in all the samples, followed by lignin and holocellulose in lower concentrations. The most affected variables throughout the industrial processing were: lignin, chloroform and water extracts and the acid fraction of waxes. These variables did not allow one to distinguish the studied trees, which are differentiated by the percentages of methanol extracts, the tannic fraction of polyphenols, the free of suberin residue and the holocellulose content. Four variables were selected as those which provided the greatest discrimination among provenances: methanol extract, low molecular weight polyphenols, desuberinized residue and acid fraction of waxes. However, the studied populations can not be clearly distinguished by their chemical composition and no relationship was found between geographical proximity of their provenances and chemical resemblance.
doi: 10.1080/02773819809349592
Keywords: chemical composition; Cork; suberin; waxes (voyant)

Chemical Characterization of Reproduction Cork from Spanish Quercus Suber - Conde, Elvira; Cadahía, Estrella; Garcia-Vallejo, Maria Conceptión; Gonźalez-Adrados, José Ramón (Journal of Wood Chemistry and Technology, 1998)
Abstract The chemical composition of Quercus suber reproduction cork was studied in planks from three different trees at different stages of their industrial processing and in samples collected in seven locations in the three main Spanish production areas. Extracts in chloroform, methanol and water, ne[ugrave]tral and acid fractions of waxes, suberin, lignin, holocellulose and pentosans, and polyphenols (low molecular weight polyphenols and tannins), were quantified. Suberin was the main component in all the samples, followed by lignin and holocellulose in lower concentrations. The most affected variables throughout the industrial processing were: lignin, chloroform and water extracts and the acid fraction of waxes. These variables did not allow one to distinguish the studied trees, which are differentiated by the percentages of methanol extracts, the tannic fraction of polyphenols, the free of suberin residue and the holocellulose content. Four variables were selected as those which provided the greatest discrimination among provenances: methanol extract, low molecular weight polyphenols, desuberinized residue and acid fraction of waxes. However, the studied populations can not be clearly distinguished by their chemical composition and no relationship was found between geographical proximity of their provenances and chemical resemblance.
doi: 10.1080/02773819809349592doi: 10.1080/02773819809349592The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: chemical composition; Cork; suberin; waxes (voyant)

Soilwater chemistry in a holm oak ( Quercus ilex) forest: inferences on biogeochemical processes for a montane-Mediterranean area - Avila, Anna; Bonilla, David; Rodà, F; Piñol, J; Neal, C (Journal of Hydrology, 1995)
Soil solution and free-flowing soilwater were sampled at various depths for 3 years in a plot of holm oak (Quercus ilex L.) in the Montseny mountains (NE Spain). The soil solution retained at -65M kPa in the mineral soil at depths of 20 and 40 cm had a different chemistry from that of throughflow under the humic layer (H-layer throughflow) and, to a lesser extent, from deep subsurface flow. The dominant mobile anion in the soil solution and the deep flow was SO:-, whereas in the H-layer, SOi- was overridden by alkalinity. H-Layer throughflow chemistry was extremely variable, in consequence of the large number of biogeochemical processes affecting it (e.g. rainfall chemistry, dry deposition, leaching from canopy and litter, decomposition), and of the quantity of water available for transport of solutes. The chemistry of the soil solution was more predictable, as it was governed mainly by nutrient uptake, cation exchange reactions and the seasonal wetting and drying cycles. The chemistry of the deep subsurface flow was often intermediate between that of the soil solution and that of the H-layer throughflow; this suggested a mixture of displaced pre-event soil solution and of H-layer throughflow circulating through preferential flow paths. With humid antecedent conditions, the chemistry of the deep subsurface flow approached that of the soil solution. The cation concentration relationships in the soil solution were strongly linear. In a homogeneous soil, cation exchange theory predicts this to be expected only for cations of the same charge, whereas cations of different charges should follow power relationships. Our results, however, are consistent with a theoretical approach involving cation exchange reactions in a highly heterogeneous environment. Indeed, our study illustrates the heterogeneous nature of the soils, as the power relationship has been obscured completely. Soilwater chemistries were markedly different from those of streamwater, particularly under dry conditions. During baseflow, the stream is fed by groundwater, and the soils are probably disconnected from the stream. During humid periods, the chemistry of the streamwater tends toward that of the deep subsurface flow. Chemical hydrograph separation indicates that, on average, stormflow water comprises an approximately one to one mixture of groundwater and deep subsurface flow.
Keywords: biogeochemistry; chemical composition; forest soils (citation); Ions; Soil depth; soil pH; soil water; temporal variation

Influence of raw-material quality and process parameters in the production of insulation cork agglomerates - Pereira, H.; Baptista, C. (European Journal of Wood and Wood Products, 1993)
{Insulation cork agglomerates are produced with different low-cost raw-materials unsuitable for other products: virgin corks (from prunmgs, thinnings anti dead trees), reproduction corks (refuse and underaged) and industrial byproducts (corkback strips). These materials were analysed in relation to chemical composition, struc- ture and trituration behaviour. The industrial byproducts diffcr significantly from the other materials due to the presence of an important amount of the unsubcriscd lignocellulosic phlocm (the back of the corkboards) in a way that is detrimental to the agglomeration process. The influence of raw-material, granulometry and process parameters (time, temperature and pressure} were studied using an experimental autoclave. Temperature is the deter- mining factor for agglomeration. Insufficient adhesion is obtained under 230 ~C and adequate agglomeration is attained only with temperatures in the range 230 300 "C. corresponding to inass losses of 10 25%.
Keywords: chemical composition; CORK AGGLOMERATES; Raw materials; structure; trituration behaviour (Voyant)

Influence of raw-material quality and process parameters in the production of insulation cork agglomerates - Pereira, H; Baptista, C (European Journal of Wood and Wood Products, 1993)
{Insulation cork agglomerates are produced with different low-cost raw-materials unsuitable for other products: virgin corks (from prunmgs, thinnings anti dead trees), reproduction corks (refuse and underaged) and industrial byproducts (corkback strips). These materials were analysed in relation to chemical composition, struc- ture and trituration behaviour. The industrial byproducts diffcr significantly from the other materials due to the presence of an important amount of the unsubcriscd lignocellulosic phlocm (the back of the corkboards) in a way that is detrimental to the agglomeration process. The influence of raw-material, granulometry and process parameters (time, temperature and pressure} were studied using an experimental autoclave. Temperature is the deter- mining factor for agglomeration. Insufficient adhesion is obtained under 230 ~C and adequate agglomeration is attained only with temperatures in the range 230 300 "C. corresponding to inass losses of 10 25%.
Keywords: chemical composition; CORK AGGLOMERATES; Raw materials; structure; trituration behaviour (Voyant)

Chemical composition and variability of cork from Quercus suber L. - Pereira, H (Wood Science and Technology, 1988)
The chemical composition of cork from Quercus suber L. was determined for virgin cork and for reproduction cork. Average chemical composition of virgin cork is: ash 0.7%, total extractives 15.3%, suberin 38.6%, lignin 21.7% and polysaccharides 18.2%. The carbo- hydrate composition shows that glucose represents 50.6% of all monosaccharides, xylose 35.0%~ arabinose 7.0% and galactose and mannose, respectively, 3.6% and 3.4%. Reproduction cork has a composition similar to virgin cork. For the cases studied, reproduction cork had however less extractives and a higher amount of suberin. Significant differences were found for the chemical composition of virgin cork in relation to location of extractives and polysaccharide content. The between-tree variability was large and a variation within the tree was also recorded.
Keywords: chemical composition; Cork; reproduction cork (voyant); virgin cork

MEDITERRANEAN SHRUBBY VEGETATION AND ITS VALORATION .6. EVOLUTION OF CHEMICAL COMPOSITION OF QUERCUS-ILEX L - PEINADOLUCENA, E; GOMEZCASTRO, A G; RODRIGUEZBERROCAL, J; MEDINACARNICER, Y M (ARCHIVOS DE ZOOTECNIA, 1978)
APS
Keywords: chemical composition; Mediterranean; Quercus ilex; shrubby vegetation